Suppressing chondrocyte cuproptosis by syringaresinol-4-O-β-d-glucoside alleviates gouty arthritis - Fu, Shaotian; Du, Han; Ling, Xiao; Wang, Hanyi; Chen, Jianan; Zhang, Hang; Chen, Wugui; Liu, Chengzhao; Ma, Hailong; Lin, Chengshou; Ma, Peixiang; Qin, An (Frontiers in Pharmacology, 2025)
BackgroundGouty arthritis is a rheumatic disease characterized by synovial inflammation and cartilage damage. Current therapeutic options for gouty arthritis, such as colchicine, primarily relieve the symptoms, which makes treatment challenging.MethodsWe employed an in vitro co-culture system of chondrocytes and macrophages to simulate gouty arthritis and screen compounds that can inhibit monosodium urate (MSU) associated macrophage inflammation and chondrocytes degeneration. We further elucidated the cuproptosis mechanism in chondrocytes by qPCR and Western blotting analyses. Both acute and chronic gouty arthritis mouse models were established to evaluate the therapeutic efficacy of candidate drugs against gouty arthritis.ResultsMSU upregulates the expression of inflammatory cytokines in macrophages and simultaneously induces cuproptosis in chondrocytes. By screening 24 compounds, we identified syringaresinol-4-O-β-d-glucoside (SSG), a furanoid lignan, as a potent inhibitor of macrophage-mediated inflammation and chondrocyte cuproptosis. Mechanistically, SSG inhibited MSU-induced activation of the NF-κB and NLRP3 pathways in macrophages. Furthermore, SSG regulated the expression of sulfur-linked mitochondrial enzymes (e.g., DLAT) in the cuproptosis pathway, thereby inhibiting the upstream regulator FDX1 in chondrocytes. SSG not only alleviated inflammatory pain but also protected against cartilage damage and improved motor dysfunction in the mice models of acute and chronic gouty arthritis.ConclusionSSG can serve as a promising therapeutic option for gouty arthritis in clinical settings by suppressing inflammation and preserving cartilage integrity.